Evolution of Lean Management and the Organizational Learning - Gurabi, Attila; Mátrai, Norbert (International Journal of Engineering and Management Sciences, 2018)
In industry, service and public sector lean approach is gaining ground. However, there is a significant difference between the organizations applying lean concept in case of their lean transformation maturity level as well as their lessons learned. There is a huge variety of methods and techniques which can be used but there are two conditions in case of every organization regardless their sector or their lean maturity level which determine the success of their lean development: lean approach leader and learning organization. Lean leadership is not based on a particular sector or method and a ready-made lean organization is not needed either. The concept of the top management has a huge effect on the characteristics of theorganization but whether the will of the management is enough for the complete transformation or not is the question. Is the target the lean organization itself or how a unit of an organization or the whole organization can react to the change of the environment? The attitudes and behaviors of lean approach leadership can be applied every day, everywhere and support the aim of creating a real lean organization.